2016
DOI: 10.3892/mmr.2016.5775
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microRNA and protein expression analysis reveals novel microRNA regulation of targets in fetal down syndrome

Abstract: Down syndrome (DS) is caused by trisomy of human chromosome 21 and is associated with a number of deleterious phenotypes. To investigate the role of microRNA (miRNA) in the regulation of DS, high-throughput Illumina sequencing technology and isobaric tagging for relative and absolute protein quantification analysis were utilized for simultaneous expression profiling of miRNA and protein in fetuses with DS and normal fetuses. A total of 344 miRNAs were associated with DS. Gene Ontology and Kyoto Encyclopedia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
1
2
Order By: Relevance
“…The six DEmiRs identified in the present study between children with DS and controls are not located on HSA21; four of them were observed to be upregulated (miR-378a-3p, miR-130b-5p, miR-942-5p, and miR-424-3p) and two downregulated (miR-452-5p and miR-668-3p). Although some DEmiRs identified in the present study have been previously found to be dysregulated in other DS tissues [35][36][37], to our knowledge, this is the first study to report altered expression of these six DEmiRs in PBMCs from individuals with DS. Altered expression of miRNAs not located on HSA21 with possible involvement in DS phenotypes has been previously reported [33][34][35][36][37][38][39][40], supporting the existing hypothesis of secondary transcriptional changes as a consequence of the trisomy 21 [41].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The six DEmiRs identified in the present study between children with DS and controls are not located on HSA21; four of them were observed to be upregulated (miR-378a-3p, miR-130b-5p, miR-942-5p, and miR-424-3p) and two downregulated (miR-452-5p and miR-668-3p). Although some DEmiRs identified in the present study have been previously found to be dysregulated in other DS tissues [35][36][37], to our knowledge, this is the first study to report altered expression of these six DEmiRs in PBMCs from individuals with DS. Altered expression of miRNAs not located on HSA21 with possible involvement in DS phenotypes has been previously reported [33][34][35][36][37][38][39][40], supporting the existing hypothesis of secondary transcriptional changes as a consequence of the trisomy 21 [41].…”
Section: Discussioncontrasting
confidence: 46%
“…Although some DEmiRs identified in the present study have been previously found to be dysregulated in other DS tissues [35][36][37], to our knowledge, this is the first study to report altered expression of these six DEmiRs in PBMCs from individuals with DS. Altered expression of miRNAs not located on HSA21 with possible involvement in DS phenotypes has been previously reported [33][34][35][36][37][38][39][40], supporting the existing hypothesis of secondary transcriptional changes as a consequence of the trisomy 21 [41].…”
Section: Discussioncontrasting
confidence: 46%
“…The first three belong to a cluster located within the C21orf34, miR-802 is located inside RUNX1, while miR-155 is located within MIR155HG (MIR155 host gene) as part of BIC (B cell integration) cluster. Bioinformatics analyses of miR(21) predict over 2000 putative targets, which suggest that if deregulated, miR(21) might play an important role in DS pathogenesis [17].…”
Section: Introductionmentioning
confidence: 99%